FACTORS INFLUENCING STIGMA AGAINST PEOPLE WITH MENTAL DISORDERS IN INDONESIA: A SYSTEMATIC REVIEW - Maximilianus Dasril Samura; Afrizal; Amel Yanis; Hardisman (RADJA PUBLIKA, 2025)
Stigma against People with Mental Disorders (ODGJ) remains a major challenge in Indonesia's mental health system. This stigma affects various aspects of their lives, from social discrimination to limited access to mental health services. This study aims to identify the factors influencing stigma against ODGJ in Indonesia through a systematic review of literature published in the last ten years. The analysis focuses on individual, familial, socio-cultural, and structural factors contributing to stigma. The findings indicate that stigma is influenced by the public's lack of understanding of mental health, social pressure experienced by ODGJ families, cultural norms linking mental disorders to mystical beliefs, and limited government policies supporting mental health services. A comprehensive approach, including mental health education, family empowerment, community-based interventions, and improved mental health policies, is needed to reduce stigma and enhance the quality of life for individuals with mental disorders.